mRNA Vaccines in Treatment Tumor: Advancement and Challenges - Cao, Wen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Immunotherapy has become a well-known cancer treatment method recently. The expeditious development of COVID-19 vaccines has made the extensive use of messenger RNA (mRNA) vaccines possible, and strikingly increased research data have been devoted to exploiting the potential of mRNA vaccines as preclinical and clinical treatments for cancer. mRNA cancer vaccines can stimulate durable and targeted immune responses against tumor antigens (TAs). Despite the promising future of mRNA vaccines, some challenges remain, including mRNA instability and safety concerns. It is possible to improve mRNA’s stability, translation efficiency, and immune-stimulating qualities by changing its components. Another main challenge facing the field of mRNA therapy is to improve the effectiveness delivery systems. This review begins with an introduction to the immunological mechanism underlying mRNA cancer vaccines. It then focuses on discussing the subject of improving the efficacy of mRNA cancer vaccines via two main approaches: optimization of mRNA structural and improvement of delivery system.